Contextual Based E-learning (CBE): A New Model for Online Teaching in Public Health Department for Learning During the Covid-19 Pandemic - Reno Renaldi; Aldiga Rienarti Abidin; Irawan, Yuda; Abdurrahman Hamid; Rizky Ema Wulansari, (International Journal of Interactive Mobile Technologies (iJIM), 2022)
In order to to support physical distancing activities in the teaching and learning process during the Covid-19 pandemic, an appropriate and effective learning model to fit the learning objectives must be developed. The CBE (Contextual Based on E-learning) learning model, developed from the Contextual Teaching Learning (CTL) model, was integrated with e-learning. This CTL learning model was chosen because this model is an innovative learning model where the process can assist students to connect learning with the context of their lives. This study aims to describe the model's effectiveness which was measured based on three aspects, namely: a) significant difference between students’ achievement in CBE model compared to that in traditional model; b) The effectiveness of CBE syntax in learning; c) Students’ perception on the new CBE model. This study is quantitative research with quasi experimental method. The results of the CBE model showed that the CBE model is significantly effective in improving students' abilities. Therefore, it can be concluded that the CBE model is proven to be effective to be implemented as new teaching model in online learning. The implication of this research is to contribute to new existing knowledge for education, and computer science and to add references to new online-based models. The limitation of this research is the effectiveness of this model described the cognitive knowledge trough students’ learning outcomes.